Gate for photic resetting of intrinsic rhythmicity of the rat suprachiasmatic nucleus under a long photoperiod - Jelínková, D; Illnerová, H; Sumová, A (Neuroscience letters, 2000)
In rats maintained under a long photoperiod and then released into darkness, the time interval enabling photic resetting of the intrinsic rhythmicity of the suprachiasmatic nucleus (SCN), namely of the rhythm in the light-induced c-Fos production, was similar to the previously reported time interval enabling high c-fos photoinduction in the SCN (Sumová, A., Trávnícková, Z., Peters, R., Schwartz, W.J. and Illnerová, H., The rat suprachiasmatic nucleus is a clock for all seasons. Proc. Natl. Acad. Sci. USA, 92 (1995) 7754-7758). The data indicate that both intervals may represent the same window for the photic sensitivity of the SCN pacemaking program.
Keywords: Circadian Rhythm; messenger RNA; protoonkogenní proteiny c-fos; Rats; Photoperiod; Light; Analysis of Variance; fotoperioda; cirkadiánní rytmus; imunohistochemie; Gene Expression Regulation; Proto-Oncogene Proteins c-fos; světlo; mužské pohlaví; Rats, Wistar; analýza rozptylu; nucleus suprachiasmaticus; krysa rodu Rattus; Suprachiasmatic Nucleus; regulace genové exprese; Immunohistochemistry; RNA, Messenger; zvířata; potkani Wistar; Male; Animals